Controlling money : the Federal Reserve and its critics - Bryant, Ralph C. (Washington, D.C. : Brookings Institution, 1983)
The central purpose of this book examines the long-standing debate between monetarists and Keynesians and to promote an informed discussion of the matters that genuinely deserve attention, that is Money.
This book is an outgrowth of a manuscript originally prepared for a February 1982 conference on current issues in U.S monetary policy sponsored by the American Enterprise Institute for Public Policy Research.
Includes bibliographical references and index.
usc 20/6/17
Loans
Keywords: Monetary policy; Money supply; United States